Assessment of Competency Based on Dicotomic Scoring to Diagnose Students 'Skills in Vocational Learning in Vocational Schools - Wahid Munawar (Journal of Vocational Education Studies, 2021)
Assessment of competency in schools is carried out by teachers using conventional tests, consists of multiple choice tests, essay tests, and skills tests using open scoring competency tests based on the teacher's principle of "being in charge" in scoring. Therefore, a assessment of competency tool is needed that measures the real competence of students. The research objective was to diagnose students' skills in automotive body vocational learning through a dichotomy scoring competency test. The research method used is pre experimental design (non designs) one shot case study. The research was conducted in January-March 2020. The research location was in a state vocational high school in Bandung. The research sample used simple random sampling of 32 students. Data collection used a dichotomy scoring skill test. Data analysis using percentages. The results showed that: (1) 84% of the students were not competent in the competence of automotive bodies in making mini cars when using the dichotomy scoring competency assessment; (2) only 16% of students were able to complete the competency test by producing work products that match dimensions and on time.Â